Eksistensi Budaya Lokal Sebagai Representasi Spiritualitas dan Sosial Keagamaan di Desa Sidorejo Kecamatan Geneng Kabupaten Ngawi - Muhammad Habibullah; Moh. Ansori (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
ABSTRACT Culture is an integral part that cannot be separated from the elements of community life in Ngawi Regency, playing an important role in illustrating identity, social, and representation of religious values ​​​​held. The existence of culture in Sidorejo Village, Geneng District, Ngawi Regency, which is still preserved in the form of Ketoprak and Manaqiban performances, this is a complementary element to always keep the village identity alive without fear of being eroded by the dynamics of modern art. This article aims to explore the large role of Ketoprak and Manaqiban arts in influencing social change that occurs in Sidorejo Village. This study uses a qualitative method with a descriptive analytical approach. Data collection uses observation, interviews and literature studies. Data analysis techniques use three methods: data reduction, data presentation, and verification or drawing conclusions. Through the noble values ​​​​upheld by culture and religion, it is possible for mutually reinforcing acculturation between the two. This finding emphasizes that the younger generation in Ngawi Regency must participate in preserving and playing an active role in all forms of cultural and religious development such as Ketoprak and Manaqiban. Keywords: Local Culture, Ketoprak, Manaqiban